The Determinants of Capital Structure of Islamic Banks in Indonesia, Malaysia, and Brunei Darussalam - Hawariyuni, Weni; Suprayitno, Aryadimas (Journal of Sustainable Economics, 2023)
This study is to determine the effect of Profitability, Liquidity, Asset Growth, Bank Size, and Asset Structure on the Capital Structure of Islamic banks in Indonesia, Malaysia, and Brunei Darussalam. The type of research used is descriptive quantitative, which is a descriptive approach with a quantitative approach. The analysis technique used is panel data regression with fixed effect model is the selected model. The population used in this study is Islamic banks in Indonesia, Malaysia, and Brunei Darussalam. The data was collected from Asian Banker website for 27 banks. The sample selected using purposive sampling method was 22 Islamic banks in Indonesia, Malaysia and Brunei Darussalam which consistently published annual reports during 2015-2021 period. Data collection was carried out using secondary data in the form of annual reports of 22 banks during the 2015-2021 period. The results showed that the Profitability and Asset Growth variables had a positive and insignificant effect on Capital Structure, Liquidity had a negative and significant effect on Capital Structure, and Bank Size and Asset Structure had a significant positive effect on Capital Structure.